2016
DOI: 10.1016/j.ebiom.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of gene therapy for the treatment of Leber's hereditary optic neuropathy

Abstract: Leber's hereditary optic neuropathy (LHON) is a disease that leads to blindness. Gene therapy has been investigated with some success, and could lead to important advancements in treating LHON. This was a prospective, open-label trial involving 9 LHON patients at Tongji Hospital, Wuhan, China, from August 2011 to December 2015. The purpose of this study was to evaluate the long-term outcomes of gene therapy for LHON. Nine LHON patients voluntarily received an intravitreal injection of rAAV2-ND4. Systemic exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 19 publications
(33 reference statements)
4
99
0
15
Order By: Relevance
“…The gene therapy clinical trial in China reported improvements of 3 lines or more in 5 of 9 G11778A LHON patients (7 of their patients were treated more than one year after visual loss) with 36 months of follow-up. 16;17 In our natural history study, 4 only 3 patients recovered vision of 3 lines or more 12 months after the onset of visual loss (7%). In our gene therapy study we observed increases in acuity of approximately 3 lines or more on the ETDRS chart in 3 of 6 patients treated within a year of visual loss.…”
Section: Discussionmentioning
confidence: 66%
“…The gene therapy clinical trial in China reported improvements of 3 lines or more in 5 of 9 G11778A LHON patients (7 of their patients were treated more than one year after visual loss) with 36 months of follow-up. 16;17 In our natural history study, 4 only 3 patients recovered vision of 3 lines or more 12 months after the onset of visual loss (7%). In our gene therapy study we observed increases in acuity of approximately 3 lines or more on the ETDRS chart in 3 of 6 patients treated within a year of visual loss.…”
Section: Discussionmentioning
confidence: 66%
“…Our research, however, has ruled out the possibility of spontaneous vision recovery. First, 1 year before clinical treatment, patients with spontaneous VA were excluded, and the improvement of VA in 9 patients treated from 3 months after treatment started to increase with a similar trend [7, 9]. Second, Lam et al [20] also conducted an in-depth study of the effect of increased spontaneous vision on gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Using pretherapy VA as the baseline, BCVA was examined using a standard logMAR acuity chart at a distance of 2.5 m (Star Kang Medical Technology Co., Ltd. Wen Zhou, China) [8, 9]. The same ophthalmologists examined the BCVA of both injected and uninjected eyes in 7 patients before gene therapy, and at 3, 6, 9, 24, and 36 months after treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to cutting-edge technologies, Sichuan University's West China Hospital in Chengdu recently announced that they are preparing to conduct the world's first human trial using CRISPR gene editing technology (16). In addition, a team of scientists from Tongji Medical College have, in collaboration with FivePlus Molecular Medicine Institute in Beijing, successfully conducted a long-term trial of gene therapy in human patients with a rare genetic disorder known as Leber's hereditary optic neuropathy (LHON) (17,18), more than 10 years after the world's first gene therapy was approved in China (19).…”
mentioning
confidence: 99%